Response of Growth and Production of Shallots (Allium Ascalonicum L) to the Application of Chicken Manure and Volcanic Ash - Pantas Simanjuntak; Chichi Josephine Manalu (Journal Research of Social Science, Economics, and Management, 2022)
The production of shallots can still be increased through technical improvements in cultivation, such as the application of organic fertilizers and the eruption of Mount Merapi (volcanic ash). Organic fertilizers have a significant role in improving the chemical and biological properties of the soil and do not have a negative impact on the environment, although the nutrient content of manure is not as high as that of artificial fertilizers. This study aims to determine the effect of chicken manure and volcanic ash on the growth and production of shallots (Allium ascalonicum L). The research method used was a factorial randomized block design (RAK) consisting of two treatment factors, namely factor I chicken manure ( A) and factor II volcanic ash (V). The results showed that the application of chicken manure had a significant effect on plant height, number of leaves, tuber diameter, tuber wet weight, tuber dry weight. Volcanic ash treatment had no significant effect on plant height, number of leaves, tuber diameter, tuber number, tuber wet weight, and tuber dry weight. The interaction between chicken manure and volcanic ash had no significant effect on plant height, number of leaves, number of tubers, tuber diameter, tuber wet weight, and tuber dry weight.